182k views
13 votes
What is Y + 4 = -3 (x +1) in standard form?

User Eric Wang
by
4.2k points

2 Answers

10 votes

Answer:

-3x - y = 7

first, distribute -3:

y + 4 = -3x - 3

then get x and y on the same side and the number on the other side for standard form.

add 3 to both sides:

y + 7 = -3x

subtract y from both sides:

7 = -3x - y

User MKoosej
by
5.3k points
11 votes
Answer:
-3x - y = 7

Step-by-step explanation:
the standard form of an equation is written as Ax + By = C, where A, B, and C are integers.
first, distribute -3:
y + 4 = -3x - 3
then get x and y on the same side and the number on the other side for standard form.
add 3 to both sides:
y + 7 = -3x
subtract y from both sides:
7 = -3x - y
User NotMyself
by
4.4k points